Who speaks up for Inés Fonseca? Representing violence against vulnerable subjects and the ethics of care in fictional narrative about Alzheimer's disease: Ahora tocad música de baile (2004) by Andrés Barba - MEDINA, RAQUEL (Ageing and society, 2017)
This paper studies the 2004 Spanish fictional novel by Andrés Barba, Ahora tocad música de baile, one of the first cultural texts dealing entirely with Alzheimer's disease to appear in Spain. It argues that the significance of Barba's fictional novel rests on two important issues: the ethics of representation of violence against vulnerable subjects and the ethics of care. The paper analyses how these two issues allow Barba to create a story in which the verbal and physical abuse to which the person living with Alzheimer's disease is subjected places the reader, on the one hand, as voyeur/witness of the abuse; and, on the other, as interpreter, and ultimately judge, of the fine line that separates euthanasia, assisted suicide and murder. The open ending of the novel defers all ethical and moral judgement to the reader. It examines how the novel offers a monolithic perspective about Alzheimer's disease, in which care is presented as a burden. In fact, this study shows that the novel's multi-layered structure and polyphonic nature places the emphasis on stigmas, stereotypes and negative metaphors around Alzheimer's disease, as found in contemporary social discourses.